Evaluation of hospitalized patients with a possible diagnosis of COVID-19: Patients with a possible diagnosis of COVID-19 - Korkmaz, Derya; Konya, Petek; Tünay, Havva; Dilek, Oğuzhan; Demirtürk, Neşe (Journal of Surgery and Medicine, 2022)
Background/Aim: The definitive diagnosis of COVID-19 disease is made by demonstrating the presence of SARS-CoV-2 in nasopharyngeal swab samples. In patients who present with COVID-19-like symptoms but are found to be PCR negative, lung tomography, physical examination, and specific laboratory findings can guide diagnosis and treatment. This study aims to retrospectively evaluate the clinical, laboratory, and radiological findings of patients who presented with Covid-19-like symptoms. but were found to be PCR negative. Methods: This study was planned as a retrospective cohort study. Patients hospitalized in the pandemic service of Afyonkarahisar Health Sciences University between 19 March and 30 September 2020 - who were PCR negative and defined as possible cases through diagnosis, treatment, and follow-up guidelines of the Republic of Turkey Ministry of Health, were included. Of these patients, those without radiological pulmonary involvement were defined as group A, and those with radiological pulmonary involvement were defined as group B. Clinical and laboratory findings of both groups were evaluated and compared. Results: In the lung tomographic examination of 238 patients in the study, 16.4% in group A without radiological lung findings and 83.6% in group B with signs of inflammation were identified. While common complaints were high fever and diarrhea in group A, cough and shortness of breath were significantly higher in group B. The most common comorbidities in both groups were hypertension and diabetes, respectively, while hypertension was found to be significantly higher in group B. There was no mortality in any patient without lung involvement, but there was no significant difference between groups in terms of mortality. Conclusion: These techniques can be used in PCR-negative patients presenting with COVID-19, for an estimation of patients with a severe prognosis with pulmonary tomography findings, symptoms, laboratory results, and accompanying disease at the time of admission. Determining parameters that identify at-risk patients during the early period may contribute to improving patient management and the appropriate use of limited resources.